Review of the Campsicnemus fumipennis group (Diptera: Dolichopodidae) in the Hawaiian Islands, with descriptions of new species and corrections of misidentifications - Evenhuis, Neal L. (Zootaxa, 2012)
Species of the Campsicnemus fumipennis group in the Hawaiian Islands are reviewed. Campsicnemus fumipennis Parent,previously thought to be widespread in the Hawaiian Islands is found to be restricted only to the islands of Moloka‘i andMaui (= geological Maui Nui). Based on comparison of the lectotype female of C. fumipennis with females of C.flaviventer Hardy & Kohn, C. flaviventer is found to be synonymous with C. fumipennis, syn. nov. Three new species,two of them previously misidentified as either C. fumipennis or C. flaviventer, are described and illustrated; all are islandendemics: C. leucostoma, sp. nov. (Hawai‘i), C. spectabulus, sp. nov. (O‘ahu), and C. aniani, sp. nov. (Hawai‘i). The firstdescription of the male of true C. fumipennis is given, a key to species of the C. fumipennis group is presented, and a table of rearing records for immatures of species in the C. fumipennis group is given.